Private Elementary School Teachers' Perceptions of Character Education Practice in Indonesia - Rigia Tirza Hardini; Sri Wening (International Journal of Theory and Application in Elementary and Secondary School Education, 2020)
Character education considered one of the ways to overcome character and morality problems. Though character education has been taught for decades, character and the moral problem still happened in our society. Lots of people agree that we need to reinforce character education to improve the performance of character education. Some institutions invented some programs to help the implementation of character education. Aware of this condition, the Indonesian government also strived to improve character education by released a program called Penguatan Pendidikan Karakter (PPK), which stands for character education reinforcement. This program expected to give schools an idea of how character education should be taught in a holistic approach, thus it can help schools implied a better character education. Long before the government releases the program, some schools, mostly private schools, already planned and implemented their own character education program. This paper elaborates private school teachers’ perspectives on character education practice in their schools. This qualitative research was conducted through interviews involving three private school teachers. The teachers teach different private schools located in Yogyakarta, Jakarta, and Lampung. Teachers' perspectives expected to help us understand the relevant practice of character education and development needs to adjust the student in this era.